Experiment of aerodynamic force on a rotating soccer ball - Hong, S.; Nobori, R.; Sakamoto, K.; Koido, M.; Nakayama, M.; Asai, T. (Procedia Engineering, 2016)
The purpose of this study was to measure the aerodynamic force acting upon a soccer ball spun in a wind-tunnel test. In particular, we prepared two types of spinning soccer balls (air and motor types), measured the aerodynamic force on each, and examined the validity of the measurement method. In the case of the air-type spinning ball, the ball was made to spin by applying compressed air from an air compressor via an air duster. In the case of the motor-type spinning ball, a motor was placed at the middle inside the ball, and the ball was then automatically spun. First, both the air- and motor-type spinning balls demonstrated very strong spin-parameter (Sp) dependence with respect to drag during spinning. In addition, the side-force coefficient showed signs of linear increase as Sp increased in the motor-type spinning ball, whereas it increased along a slight curve in the air-type spinning ball. In particular, a negative Magnus effect was observed in the motor-type spinning ball when the Reynolds number was approximately 2.0 x 105 and Sp was approximately 0.14 (-0.007) and when the Reynolds number was approximately 2.2 x 105 and Sp was approximately 0.13 (-0.005).